Lip cancer: retrospective analysis of 181 cases - Géraud, Cyrill; Koenen, Wolfgang; Neumayr, Ludwig; Doobe, Gunnar; Schmieder, Astrid; Weiß, Christel; Goerdt, Sergij; Faulhaber, Jörg (Journal der Deutschen Dermatologischen Gesellschaft, 2012)
Background: In Germany little data on the epidemiology and histology of lip cancers are available, as lip cancers are commonly pooled together with head and neck tumors. Patients and methods: Retrospective analysis of 181 patients with malignant tumors of the lips with respect to gender, location, histology, risk factors and comorbidity. Results: There were 90 women and 91 men with a mean age of 71 years. 98 had a tumor on the upper lip and 83 patients on the lower lip. Tumors of the upper lip showed a slight female preference (61%). In contrast lower lip cancer was more common (64%) in men. Histological analysis revealed that in both regions nodular basal cell carcinomas as well as squamous cell carcinomas (NOS) are the most common subtypes. Vertical tumor thickness of squamous cell carcinomas was in most cases smaller than 6 mm (n = 71) and only in 4 cases was a tumor thickness of >6 mm detected. Altogether, 57% of the patients reported a high to very high sun exposure. Conclusions: In comparison to previous studies we found a weaker preference for women for tumors of the upper lip and also a weaker preference for men for tumors of the lower lip. The causes remain unclear, but could be causally related to an increased life expectancy and/or changed risk profile.